How Referential Gestures Align With Speech: Evidence From Monolingual and Bilingual Speakers. Issue 1 (23rd August 2019) - Graziano, Maria; Nicoladis, Elena; Marentette, Paula
Abstract: When speaking, people often produce gestures that are closely timed with the speech with which they constitute a semantically coherent unit. Analyzing the temporal patterns between the two modalities may reveal insights about how speakers plan them. Using elicited narratives, we tested English/French monolinguals and bilinguals to check whether bilinguals, known to experience a higher degree of competition in lexical access, show a different pattern of gesture–speech alignment compared to that of monolinguals. Results revealed no difference in the temporal patterns between gestures and co‐semantic speech for the two language groups. Synchronous gestures were significantly more frequent than asynchronous ones; asynchronous gestures both preceded and followed the correlated speech, yet preceding gestures tended to occur more often. A qualitative analysis conducted for asynchronous gestures revealed that they may serve a rhetoric function. We argue that the variability in gesture–speech timing results from speakers' strategic use of gesture. Abstract :